A citywide, clonal outbreak of Pseudomonas aeruginosa. (April 2022) - Opperman, Christoffel J.; Moodley, Clinton; Lennard, Katie; Smith, Mariette; Ncayiyana, Jabulani; Vulindlu, Mjikisile; Gafoor, Musarrat; Govender, Nevashan; Ismail, Husna; Bamford, Colleen; McCarthy, Kerrigan M.; Nicol, Mark P.; et al.
Highlights: A citywide clonal outbreak of community-acquired P. aeruginosa was identified The outbreak coincided with a severe drought in Cape Town, South Africa The multilocus sequence type 303 was identified as the outbreak clone ST303 had virulence factors for biofilm formation, iron uptake, and gut penetration Abstract: Background: Outbreaks of community-acquired Pseudomonas aeruginosa are typically small and localized. We investigated an increase in community-acquired infections with P. aeruginosa in Cape Town, South Africa. Methods: Cases were defined as P. aeruginosa isolated from any clinical sample, and "wild-type" as those susceptible to all antibiotics tested. The residential addresses of community-acquired wild-type cases were mapped. Whole-genome sequencing and multilocus sequence typing were used to determine clonality and identify virulence genes. A clinical study in a subset of patients with bloodstream infection compared demographic and clinical characteristics between sequence types (STs). Results: The outbreak lasted 10 months from December 2016 to September 2017 with 3, 321 documented cases. At the peak, cases reached 2.3-fold baseline rates. Cases were distributed widely across the city. Multilocus ST 303 was predominant during the outbreak. A total of 51 virulence genes were differentially present in ST303 compared with other STs, including genes involved in biofilm formation, iron uptake, and gut penetration. Conclusion: The investigation confirmed a citywide outbreak of P. aeruginosa . We identified a predominant outbreak-associated clone, ST303, which harbored genes that could contribute to virulence and survival in adverse environmental conditions such as those associated with drought.